Analisis Dampak Kebijakan Otoritas Jasa Keuangan (OJK) Terhadap Pertumbuhan Perbankan Syariah di Indonesia (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
This study aims to examine how Financial Services Authority (OJK) regulations have affected the rapid expansion of Indonesia’s sharia banking industry amid digital and international economic challenges. The primary focus is on the Indonesian Sharia Banking Development and Strengthening Roadmap (RP3SI) and the requirement to separate (spin-off) Sharia Business Units (UUS) as stipulated in OJK Regulation (POJK) Number 12 of 2023.A qualitative descriptive research approach was used, employing policy analysis techniques and an examination of secondary data from the Sharia Financial Development Report.Analysis findings indicate that OJK regulations have significantly improved sharia banking capital and governance through consolidation incentives. Regulatory intervention in digitalization has also proven effective in enhancing operational efficiency and expanding service reach to the public. However, the study identifies challenges in policy synchronization, as asset growth has not been matched by a linear increase in market share, which remains below 10%. Key barriers include limited product differentiation and low levels of public sharia financial literacy.The conclusion emphasizes that while OJK policies provide a strong legal foundation for industry stability, more progressive incentives and cross-sector collaboration within the halal economic ecosystem are needed to drive more exponential growth. This study offers important implications for regulators to evaluate policy communication strategies to better adapt to market dynamics